Hierarchical zinc oxide nano-tips and micro-rods: hydrothermal synthesis and improved chemi-resistive response towards ethanol. Issue 2 (23rd December 2015) - Das, P.; Mondal, B.; Mukherjee, K.
Abstract : In the present work, a novel hierarchical architecture of zinc oxide has been synthesized through a spherical carbon template assisted two step hydrothermal process. Abstract : In the present work, a novel hierarchical architecture of zinc oxide has been synthesized through a spherical carbon template assisted two step hydrothermal process. The architecture can be represented visually as a combination of secondary phase nano-tips grown on initially prepared zinc oxide micro rods. An attempt has been made here to understand the mechanism for the formation of the said zinc oxide architecture. As compared to the zinc oxide micro rods, the enhanced surface activity of the hierarchical architecture has been reflected during its improved chemi-resistive response towards ethanol. The sensing characteristics are measured by varying the sensor operating temperature (250–350 °C) and ethanol concentrations (50–200 ppm). The prepared micro rods and hierarchical architecture show 47 and 59% responses towards 50 ppm ethanol at their optimum operating temperature of 325 °C.